2011
DOI: 10.1002/adma.201101514
|View full text |Cite
|
Sign up to set email alerts
|

Polarizing Organic Photovoltaics

Abstract: Polarizing organic photovoltaic (ZOPV) technology is demonstrated as a novel concept for energy harvesting and recycling technology. Novel, inverted quasi‐bilayer device architecture is utilized to realize the ZOPV device. An anisotropic photovoltaic effect is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 34 publications
1
123
1
Order By: Relevance
“…These unique properties of PSCs opened a new gateway for new applications in the formation of stretchable solar devices including textiles and fabrics [39]. A modern recycling concept known as polarizing organic photovoltaics (ZOPVs) was also developed for increasing the function of liquid crystal displays utilizing the same polarizer, a photovoltaic device and proper light conditions/solar panel [39]- [41].…”
Section: Nano Crystal Based Solar Cellsmentioning
confidence: 99%
“…These unique properties of PSCs opened a new gateway for new applications in the formation of stretchable solar devices including textiles and fabrics [39]. A modern recycling concept known as polarizing organic photovoltaics (ZOPVs) was also developed for increasing the function of liquid crystal displays utilizing the same polarizer, a photovoltaic device and proper light conditions/solar panel [39]- [41].…”
Section: Nano Crystal Based Solar Cellsmentioning
confidence: 99%
“…124 Another new use for SqP is as a means to control donor/acceptor vertical phase separation in BHJ films. Several groups have shown that a charge extraction misbalance due to an improper active layer/electrode interface can cause a reduction in the device fill factor, giving an S-shaped current− voltage curve.…”
Section: +mentioning
confidence: 99%
“…Since Tang published the first organic heterojunction solar cell in 1986, the energy harvesting efficiency of OPVs have greatly increased due to optimized electronic device structures and incorporating novel absorber materials [1][2][3][4]. Besides the pursuit of high power efficiency, OPVs have also been investigated for various potential applications [5,6]. Transparent OPVs, i.e., devices that seem transparent to the human eye due to high transmissivity between 400 nm -700 nm, can be integrated into window panes or screens of consumer electronic devices [7].…”
Section: Introductionmentioning
confidence: 99%